NUTRIENT MEDIUM SELECTION AND OPTIMIZATION OF AVIBACTERIUM PARAGALLINARUM DEEP CULTURE METHOD - M. S. Firsova; V. A. Yevgrafova; A. V. Potekhin (Ветеринария сегодня)
Different liquid nutrient media supplemented with growth factors intended for Avibacterium paragallinarum strain No. 5111 cultivation were compared. The highest specific growth rate (μ = 0.787 ± 0.041 h-1) and the maximal accumulation of the agent’s biomass (Х = 9.52 ± 0.04 lg CFU/ cm3) were reported when cultured in casein soybean broth. Herewith, the mean time of the live microbial cell concentration doubling was minimal (td = 0.88 h), and the exponential growth phase lasted for 6 hours. The optimal method for Avibacterium paragallinarum cultivation in casein soybean broth in laboratory bioreactor Biotron LiFlus GX was determined through the measurements and adjustment of basic physical and chemical parameters. The time period until the culture reached the stationary growth phase was maximal with aeration at 1.0 l/min; herewith, the O2 partial pressure in the nutrient medium did not exceed 25%. The period of the intense decrease of medium’s pH was accompanied with the exponential phase of the bacterial growth. The nutrient medium’s pH ranging from 7.30 ± 0.02 to 7.90 ± 0.06 had no significant impact on the specific growth rate of the strain and the lag phase duration was minimal – 0.36–0.45 h. The strain cultivation in the nutrient medium with pH 7.90 ± 0.06 demonstrated maximal aggregation of the bacteria (9.76 ± 0.04 lg CFU/cm3). 40% glucose solution added at 0.6-0.8 g/l during cultivation facilitated the decrease of the suspension’s pH. Minimal redox value (–75 mV) was indicative of the completion of the exponential phase of the strain growth.